Effect of additive interference on speech transmission - Brachmański, S. (Archives of Acoustics, 2002)
This paper presents the relationship between logatom intelligibility of Polish speech and a level of masking random noise. Subjective measurements of intelligibility were carried out for optimal speech signal level 85 dBA and signal to noise ratio within a range from -15 dBA to +15 dBA. The influence of the frequency distortion (band limiting) was investigated for three cases of a band with: 100-6000 Hz, 400-2500 Hz and 300-3400 Hz. The obtained results are shown as a curve describing a relation between a logatom intelligibility and signal to noise ratio (S/N). The obtained characteristics were compared with a standard curve given in ISO Recommendation for a two-ears listening test.